The Influence of Product Quality, Product Innovation, and Consumer Be-havior on the Purchase Decision of Iphone Products in Batam City - Jayanto, Ricky; Realize (Institute for Law and Economics Studies, 2025)
The development of the times encourages each technology company to be able to create products that can be adjusted to the latest consumer needs, especially communication technology. These products, in addition to being able to meet their needs, must be able to help complete daily work and provide added value during their use. This study aims to examine whether there is an influence involved from product quality variables, product innovation and consumer behavior on the purchase decision of Iphone products in Batam City. The research method applied in this research process is to use the Lemeshow formula so that as many as 100 respondents were obtained with a side non-probability sampling technique by purposive sampling. The results obtained were that each independent variable gave significant and positive results where the variables of product quality, product innovation, and consumer behavior to the dependent variable, namely the decision to purchase Iphone products in Batam City